Pengaruh Terapi Bermain Playdough Terhadap Perkembangan Motorik Halus Anak Dengan Autisme: Literature Review - Bunga; IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2025)
Background: Growth and development go hand in hand to achieve optimal child health. Growth and development are strongly influenced by the environment, a well-maintained environment will affect children's health. Acute or chronic diseases can infect children's age, for this reason the role of parents is to anticipate every child's growth and development. Children with developmental disorders such as children with autism require stimulation to stimulate motor development. Fine motor development in children with autism can be stimulated using playdough play tools. Objective: To determine the effect of playdough therapy on fine motor development in children with autism. Methods: This research design uses literature review of 6 articles through google scholar search. Results: The six articles reviewed showed the effect of playdough therapy on fine motor development in children with autism. Conclusion: Playdough therapy can affect the fine .